Breaking the rules. Ir and Business - Huibers, Theo; Wondergem, Bernd (Revista General de Información y Documentación, 2009)
The emergence of advanced information retrieval technologies has caused a drastic change in business models, in the nature of information intermediaries and in its automated processing. The characteristics of these changes and their economic consequences are analyzed.